1988
DOI: 10.1177/153331758800300309
|View full text |Cite
|
Sign up to set email alerts
|

An in-hospital respite program for Alzheimer's

Abstract: A wide-range of respite services have been developed to meet the needs of families who care for the chronically ill and frail elderly. Institutional respite is a particular service that provides inpatient care to patients and offers their families temporary relief from the strain of continuous caregiving. This paper describes a two-week in-hospital respite program specifically designed for patients with Alzheimer's disease. Patients are profiled on the use of respite, sociodemographic characteristics, function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Patients in this study, even those classified as having less severe DAT, were, in general, more severely affected than most demented patients residing in nursing homes 34 . Most study subjects were married, and their spouses and other family members had cared for them in the community for as long as was possible, assisted by close medical supervision, 36 community resources, support groups, 37 and respite programs 38,39 . Thus, by the time of admission for long‐term care, most patients were severely demented.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Patients in this study, even those classified as having less severe DAT, were, in general, more severely affected than most demented patients residing in nursing homes 34 . Most study subjects were married, and their spouses and other family members had cared for them in the community for as long as was possible, assisted by close medical supervision, 36 community resources, support groups, 37 and respite programs 38,39 . Thus, by the time of admission for long‐term care, most patients were severely demented.…”
Section: Discussionmentioning
confidence: 76%
“…and respite programs. ": 39 Thus, by the time of admission for long-term care, most patients were severely demented. Fewer subjects in TLTC were married, and this may account for their earlier admission to long-term care.…”
Section: Discussionmentioning
confidence: 99%
“…A mixture of experimental, survey and qualitative studies found usage to be low even when carers were informed of and provided with various respite services, often at subsidised or no financial cost (Adler , Cox , Larkin et al . , Montgomery , Australian Institute of Health and Welfare ). Strang and Haughey () proposed that accepting and obtaining respite services involved three steps for the carer:…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, it is somewhat surprising that the actual usage of formal respite services by carers of persons with dementia has been repeatedly shown to be relatively low (Larkin et al . , Montgomery , Cox , Braithwaite , Choi & Liu , Zarit et al . , Robinson et al .…”
Section: Introductionmentioning
confidence: 99%